2018
DOI: 10.1097/md.0000000000009820
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-146a/b correlates with inflammatory cytokines in COPD and could predict the risk of acute exacerbation COPD

Abstract: The aim of this study was to investigate the predicting value of miR-146a/b for acute exacerbation chronic obstructive pulmonary disease (AECOPD) and COPD, and to explore their associations with inflammatory cytokines in AECOPD and stable COPD patients.One hundred six AECOPD, 122 stable COPD patients, and 110 health volunteers with age and sex matched to total COPD patients (AECOPD and stable COPD) were enrolled. Blood samples were collected from all participants. Relative expression of miR-146a/b was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
0
22
1
1
Order By: Relevance
“…Single nucleotide polymorphisms of miR-146a were associated with the lung function in COPD smokers [39,40]. In contrast to our study, a study showed significantly decreased serum miR-146a level in COPD patients with acute exacerbation as compared with stable COPD patients and healthy controls, while no significant difference was observed in serum miR-146a level between stable COPD patients and healthy controls [41]. Several studies showed the important role of miR-146a-5p in the aberrant epithelial-fibroblast crosstalk in COPD [42].…”
Section: Discussioncontrasting
confidence: 87%
“…Single nucleotide polymorphisms of miR-146a were associated with the lung function in COPD smokers [39,40]. In contrast to our study, a study showed significantly decreased serum miR-146a level in COPD patients with acute exacerbation as compared with stable COPD patients and healthy controls, while no significant difference was observed in serum miR-146a level between stable COPD patients and healthy controls [41]. Several studies showed the important role of miR-146a-5p in the aberrant epithelial-fibroblast crosstalk in COPD [42].…”
Section: Discussioncontrasting
confidence: 87%
“…Downregulated in fibroblasts of COPD patients. Inversely correlated with the level of miR-146a and inflammation in alveolar epithelial cells Involved in epithelial–fibroblast communication, supporting its role in proinflammatory signaling [ 9 , 60 , 61 ] miR-149-3p up up up Upregulated in bronchoscopy samples of asthma patients. Downregulated in gingival periapical lesions Involved in inflammatory response [ 52 , 54 ] miR-150-3p up Upregulated in periodontitis patients Unknown [ 50 ] miR-200b down Upregulated in inflamed gingiva (the discrepancy could be attributable to the sample type: organotypic gingival cultures comprise only keratinocytes, whereas biopsy samples include different cell types, such as inflammatory cells and fibroblasts) Unknown [ 50 ] “-” indicates no specific association with the culture type.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the expression of miRNAs in biofluids has been studied as a potential marker of lung injury [ 2 , 8 ]. In a previous study, in blood samples from patients with chronic obstructive pulmonary disease (COPD), the levels of miR-146a/b were inversely correlated with the levels of inflammatory mediators; the authors proposed that miR-146a/b could serve as biomarkers for predicting the risk of acute exacerbation of COPD [ 9 ]. Other studies have proposed that some miRNAs detected in salivary and periodontal tissues could be biomarkers for periodontal pathologies [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Altered miRNAs expression was reported in several studies performed on different samples as sputum, serum and lung tissue of patients with COPD when compared to smokers without the disease. 10 , 12 , 17 , 36 , 37 Dysregulated miRNAs were observed in relation to COPD, and in relation clinical severity 18 and to increase the risk of acute exacerbations in stable patients with COPD. 37 …”
Section: Discussionmentioning
confidence: 99%